Decoding the Mechanistic Interplay of JAK/STAT and MAPK Signaling in the Pathogenesis of COPD: Crosstalk Dynamics and Multi-Target Therapeutic Frontiers - Rika Sari Dewi; Melva Louisa; Ni Made Dwi Sandhiutami; Adityo Wibowo; Irandi Putra Pratomo (Jurnal Respirasi, 2026)
The Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling cascade constitutes an intracellular communication framework that is responsive to cytokines and growth factors, whereas the mitogen-activated protein kinase (MAPK) pathway represents a signaling network activated by extrinsic stimuli such as stress, growth factors, or reactive oxygen species (ROS). This literature review synthesizes scholarly investigations into the roles of the JAK/STAT and MAPK signaling pathways in the progression of chronic obstructive pulmonary disease (COPD), with an emphasis on elucidating the molecular interactions and mechanisms that underlie deficiencies in understanding their contributions to inflammation, immune modulation, and tissue remodeling. The objectives of this review were to assess pathway activation patterns, characterize the molecular structures, and compare the therapeutic strategies. A systematic analysis of multidisciplinary studies employing in vitro, in vivo, clinical, and bioinformatics approaches was conducted. The findings revealed consistent activation of STAT3 and p38 MAPK isoforms by cigarette smoke and inflammatory stimuli, with complex crosstalk shaping macrophage polarization and cytokine production (interleukin-6/IL-6, tumor necrosis factor-α/TNF-α). Therapeutic interventions targeting JAK/STAT and MAPK signaling have the potential to reduce airway inflammation and remodeling, although clinical efficacy remains inconsistent due to corticosteroid resistance and activation of compensatory pathways. Pathway dysregulation correlates with accelerated COPD progression, particularly through epithelial-mesenchymal transition (EMT) and extracellular matrix deposition. Key challenges include balancing pathway modulation to preserve lung homeostasis while avoiding immunosuppressive effects. This analysis highlights the need for precision-targeting strategies to translate molecular insights into effective therapies, thereby providing a framework for future research on COPD pathogenesis and targeted network modulation.